Measurement and Evaluation of Human Vital Sign using 77GHz AWR1642 FMCW Radar Sensor - Srihari, Pathipati; Vandana, G s; Raghavendra, B s (Annual IEEE India Conference, 2021)
This paper proposes vital sign measurements of humans like heart rate (HR) and respiration rate (RR). The Texas Instruments AWR1642, frequency modulated continuous wave (FMCW) mmwave radar sensor, operating as 77-81 GHz frequency with 4GHz as the sweep bandwidth of the linear frequency modulated (LFM) waveform, is deployed to measure the HR and RR vital parameters. Here, twenty subjects (10 male; 10 female) experimental data has been collected using TI AWR1642 radar sensor, personal computer (PC), and DCA1000 data acquisition module. The HR and RR algorithm is applied to the process data to measure the HR and RR of these subjects. The male and female subjects' average HR is 78.587 and 77.827, respectively. Further, the average RR of the male and female subjects is 19.959 and 19.23, respectively. Furthermore, a pulse oximeter(POM) obtains HR ground truth information to validate the proposed method. The overall absolute mean error percentage(MEP) compared to pulse oximeter data is 4.7935% for 20 volunteers who have participated in the experiment.